Study on population of synanthropic fly in UiTM Negeri Sembilan, Kuala Pilah Campus / Siti Zulaifah Abdullah - Abdullah, Siti Zulaifah (Faculty of Applied Sciences, 2015)
The study on population of synanthropic fly in Universiti Teknologi MARA Negeri Sembilan, Kuala Pilah campus was done at three different sites; at a food outlet (site A), at academic building (site B), and at administration building (site C). The objectives of this study are to estimate the population of synanthropic flies at three different sites and to identify the species of synanthropic flies which exist in UiTM Negeri Sembilan, campus Kuala Pilah.The study included two weeks of sampling duration in November to December 2014. Four type of synanthropic fly species were found which are Musca domestica, M. sorbens, Chrysomya megacephala, and Lucilia cuprina with total of 935 individuals caught. They are from two family, Muscidae and Calliphoridae. M. domestica was found as the most prevalent species at all three sites; site A (88.6%), site B (97.57%) and site C (98.9%).It is followed C. megacephala; site A (9.46%), site B (2.43%) and site C (1.1%). The least population is L. cuprina, (0.65%) which is only found in site A and another species that only found in site A is M. sorbens (1.29%)